Delinquencies in the confinement of Covid-19 in the Rural Savings and Root Credit Fund, Perú - Periche-Delgado, Greicy S. (2020)
Delinquency is a highly relevant variable for a financial institution, since through the delinquency index it allows to measure the performance of the entities. Therefore, the research has been carried out with the purpose of describing the evolution of delinquencies in the confinement of Covid-19, in the Rural Savings and Credit Root Fund. The study had a non-experimental design, with a quantitative and descriptive approach, the population consisted of 44 between agencies and offices distributed nationwide. Among the instruments applied was the document analysis guide. The results showed that the company between 2016 and 2020 delinquencies presented an increasing trend, due to microeconomic and macroeconomic factors, the latter due to the global crisis caused by Covid-19. Therefore, it is concluded that the increase in delinquencies between the analyzed period was influenced by the non-compliance of credit payments between the first 30 and 60 days, as a result of the purchasing deficit and / or conjunctural problems on the part of the clients, and currently due to the coronavirus pandemic in which the majority of Peruvians have been economically affected.